What Drives Carbon Emissions in German Manufacturing: Scale, Technique or Composition? - Elisa Rottner; Kathrine von Graevenitz (Environmental and Resource Economics, 2024)
AbstractEmissions of local pollutants from industry have declined across many developed countries over the last decades. For carbon emissions such reductions have yet to materialize. Using German administrative micro-data at the product level, we apply the workhorse model for decomposing emission changes into scale, composition (changes in the mix of goods produced) and technology (emission factors of production) effects. We find that the production composition in German manufacturing shifted towards less CO2 intensive goods, while emission intensities of production increased. We show that data aggregation matters. Both effects are substantially underestimated when using data at the sector level as compared to the product level. A complementary plant level decomposition reveals that emission intensities of production increased both within plant, and due to a reallocation of production to more emission intensive plants.
Keywords: D22; L60; Q41; Q48; 330; Carbon emissions; Climate policy; Statistical decomposition; Manufacturing